Implementing Jakob Nielsenâs 10 Heuristics of usability in development of web based dental system (WEBDENT) - Nur Fadhilah, Che Nordin (2012)
The majority of work on computer use in the dental field has focused on non-clinical practice management information needs. Very few computer-based dental information systems provide management support of the clinical care process, particularly with respect to quality management.Traditional quality assurance methods rely on the paper record and provide only retrospective analysis.Today,proactive quality management initiatives are on the rise.Computer-based dental information systems are being integrated into the care environment,actively providing decision support as patient care is being delivered.These new systems emphasize assessment and improvement of patient care at the time of treatment,thus building internal quality management into the care giving process.The integration of real time quality management and patient care will be expedited by the introduction of an information system architecture that emulates the gathering and storage of clinical care data currently provided by the paper record.This paper proposes a methodology for developing web based dental system by implementing Jakob Nielsenâs 10 heuristics of usability that help making WebDent more user friendly and efficient through interactive tooth chart.The goal is to develop web based dental system for dental clinic in Malaysia and to simplify patient follow up practicable information support.The findings reveal that Web Based Dental System was developed for dental clinics in Malaysia. The automated patient record system will replace the manual dental record system and the patient follow up appointment will be simplified.